2019
DOI: 10.1103/physreve.99.052216
|View full text |Cite
|
Sign up to set email alerts
|

Lateral inhibition provides a unifying framework for spatiotemporal pattern formation in media comprising relaxation oscillators

Abstract: The collective dynamics seen in a wide variety of chemical, biological and ecological systems involve interactions between relaxation oscillators that typically involve fast activation process coupled with a slower inactivation. In this paper, we show that systems of such oscillators having distinct kinetics governing local dynamical behavior and whose interactions are described by different connection topologies, can exhibit strikingly similar spatiotemporal patterns when diffusively coupled via their inactiv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…We report here, the existence of chimera pattern that comprises neurons exhibiting both oscillatory and non-oscillatory states. Such chimera patterns have been reported in our earlier study [61] in the context of biological pattern formation. Studies on networks of excitatory and/or inhibitory with synapse and gapjunctions have shown to give complex spatiotemporal dynamics, viz.…”
Section: Discussionsupporting
confidence: 86%
“…We report here, the existence of chimera pattern that comprises neurons exhibiting both oscillatory and non-oscillatory states. Such chimera patterns have been reported in our earlier study [61] in the context of biological pattern formation. Studies on networks of excitatory and/or inhibitory with synapse and gapjunctions have shown to give complex spatiotemporal dynamics, viz.…”
Section: Discussionsupporting
confidence: 86%
“…Our work also suggests a causal relation between the simultaneous increase in regularity of the L052401-4 planar arrangement of cells in growing epithelial tissue and the arrest of growth in the cellular assembly in normal development (i.e., strong coupling) [40,50,51]. It further suggests that heterogeneous contact topology in networks of oscillators interacting via lateral inhibition [52] will increase the range over which chimera states, characterized by the coexistence of oscillating and nonoscillating elements [53], are likely to occur.…”
mentioning
confidence: 51%
“…Thus, our results suggest a causal relation between the observation of the simultaneous increase in regularity in the planar arrangement of cells in growing epithelial tissue and the arrest of growth in the cellular assembly, that occur together over the normal course of development [34,44,45]. Indeed, it hints that, in general, heterogeneous contact topology in networks of oscillators interacting via lateral inhibition [46] will increase the range of interaction strengths over which chimera states, characterized by coexistence of oscillating and non-oscillating elements [47], are likely to appear.…”
mentioning
confidence: 69%